Front Cover: Electrolyte Engineering Stabilizes Photoanodes Decorated with Molecular Catalysts (ChemSusChem 7/2023). Issue 7 (23rd March 2023) - Jenewein, Ken J.; Wang, Yuanxing; Liu, Tianying; McDonald, Tara; Zlatar, Matej; Kulyk, Nadiia; Benavente Llorente, Victoria; Kormányos, Attila; Wang, Dunwei; Cherevko, Serhiy
Abstract : The Front Cover shows a date night between hematite and a molecular iridium catalyst used as a hybrid photoanode for solar water splitting. As the night progresses, the "stability" of their relationship evolves with it, spending their best time at around pH 9. Tuning the system parameters such as the electrolyte pH can have a great impact on the activity and stability of a photoelectrochemical system and should be chosen with care when designing advanced photoanodes. More information can be found in the Research Article by K. J. Jenewein et al .